2021
DOI: 10.1021/acsomega.1c02149
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Synthesis and Catalytic Efficacy of Silver Nanoparticles Based on Peel Extracts of Citrus macroptera Fruit

Abstract: Biogenically synthesized silver nanoparticles (AgNP) increase the fascination over chemical ones due to their facile and green synthetic process. This study reports the development of an eco-friendly and cost-effective synthesis of AgNPs using an aqueous extract of Citrus macroptera fruit peel, an agricultural waste, as a sole agent with both reducing and capping abilities. The formation of AgNPs was verified by the surface plasmon resonance peak at 426 nm in the UV−vis spectrum, X-ray diffraction pattern, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…The authors concluded that bio-AgNPs can be used as powerful tools for reducing environmental pollution from organic dyes [221]. The reduction of 4-NP to 4-AP and the degradation of methyl orange (MO) and MB in the presence of sodium borohydride and catalyzed by bio-AgNPs synthesized using aqueous extract of fruit peel (Citrus macroptera) and bacteria (Bacillus cereus) were also reported recently [190,222]. Considering the above facts, it can be inferred that bio-AgNPs can be used as catalysts for the degradation of dyes.…”
Section: Catalytic Activitymentioning
confidence: 82%
See 1 more Smart Citation
“…The authors concluded that bio-AgNPs can be used as powerful tools for reducing environmental pollution from organic dyes [221]. The reduction of 4-NP to 4-AP and the degradation of methyl orange (MO) and MB in the presence of sodium borohydride and catalyzed by bio-AgNPs synthesized using aqueous extract of fruit peel (Citrus macroptera) and bacteria (Bacillus cereus) were also reported recently [190,222]. Considering the above facts, it can be inferred that bio-AgNPs can be used as catalysts for the degradation of dyes.…”
Section: Catalytic Activitymentioning
confidence: 82%
“…Biogenic AgNPs act as catalysts for the degradation of organic dyes (methylene blue, methyl orange, congo red tartrazine, carmoisine, and brilliant blue FCF) and other toxic compounds such as 4-nitrophenol to non-toxic compounds [220][221][222], which reduces environmental pollution [221]. Bio-AgNPs synthesized from aqueous Prosopis juliflora leaves extract were evaluated for catalytic activity against azo dyes such a methylene blue (MB) and congo red (CR) that resulted in its effective degradation of toxic compounds in a short span of time.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…The other signals can be attributed to the organic capping layer. The significant intensity of the peaks indicates the presence of a sufficient coating layer on the biosynthesized AgNPs [ 27 , 61 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The dense peak corresponding with silver strongly confirmed the reduction of AgNO 3 and the formation of AgNPs. An EDX analysis also proved that the required phase of silver was present in the biosynthesized AgNPs [ 27 , 61 , 63 , 76 , 91 ]. The crystalline nature of the biosynthesized AgNPs was confirmed in the form of XRD diffraction peaks at 2θ = 37°, 49°, 63°, and 76° (corresponding to the planes of silver 111, 200, 220, 311), respectively ( Figure 4 ), which are typical XRD values of biosynthesized AgNPs [ 65 , 76 , 92 , 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation